Exploring policies and initiatives for online workers in the Philippines - Ramonette B. Serafica; Queen Cel A. Oren (Philippine Institute for Development Studies (PIDS), 2022)
Digitalization has created new forms of work and work arrangements. While online work offers economic opportunities, it also raises issues in ensuring decent work. As such, the government is increasingly paying attention to the welfare of online workers and the challenges they face. To understand the policy environment shaping online work, this study examines existing and proposed laws in the Philippines and various initiatives relevant to online work using Heeks' overlapping domains of decent work as an organizing framework. It also discusses the issues surrounding platform work, particularly the vagueness of the employment status of online work, which complicate access to social protection and other benefits, as well as tax contribution. Recommendations are provided to help in the formulation of policies and programs that will benefit online workers. These include updating existing social protection programs to accommodate various types of online workers, collaboration between education and training institutions and public-private partnerships to equip online workers for employment, collection of data on the digital economy to guide government programs, and greater social dialogue between the government and stakeholders to improve working conditions of online workers.
Keywords: 330; online work; digital work; decent work; platform work